Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0363546519887167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Contraceptive Hormones on Anterior Cruciate Ligament Strength

Abstract: Background: Women are 2 to 9 times more likely to experience an anterior cruciate ligament (ACL) injury than men. Various hormones including relaxin, progesterone, and estrogen influence ACL strength. Oral contraceptives (OCs) alter these hormone levels; however, studies have yet to comprehensively compare different OCs’ effects on the ACL. Hypothesis: OCs with increased progestin-to-estrogen ratios will (1) increase ACL collagen expression, (2) decrease ACL matrix metalloproteinase expression, and (3) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
(63 reference statements)
0
3
0
1
Order By: Relevance
“…Recently, the impact of the route of estrogen administration on bone turnover markers in oligoamenorrheic athletes and its mediators [ 98 ] was demonstrated, and Ackerman et al [ 99 ] reported lumbar spine and femoral neck BMD improvement with transdermal estradiol plus cyclic oral progesterone but not with COC administration in oligo-/AM athletes. In parallel, different studies have suggested a potential 20% reduction in risk of ACL rupture under COCs [ 81 , 100 , 101 ]. It was hypothesized that the relative progestative dominance in COCs mitigates the estrogen effect [ 81 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Recently, the impact of the route of estrogen administration on bone turnover markers in oligoamenorrheic athletes and its mediators [ 98 ] was demonstrated, and Ackerman et al [ 99 ] reported lumbar spine and femoral neck BMD improvement with transdermal estradiol plus cyclic oral progesterone but not with COC administration in oligo-/AM athletes. In parallel, different studies have suggested a potential 20% reduction in risk of ACL rupture under COCs [ 81 , 100 , 101 ]. It was hypothesized that the relative progestative dominance in COCs mitigates the estrogen effect [ 81 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Diese Erkenntnis hinsichtlich Regulierung des Satellitenzellfachs bei Frauen durch Östrogen und einer verbesserten Muskelregeneration teilen auch Collins et al 1 . Einer Studie von Konopka et al 7 zufolge könnte ein höheres Gestagen-Östrogen-Verhältnis Sportlerinnen bei der Verletzungsprävention des vorderen Kreuzbands zugutekommen. Der erhöhte Hormonspiegel senke die Wirkung von Relaxin auf dieses.…”
Section: Physiologieunclassified
“…Extrinsic factors, which are modifiable, encompass the type of sport, level of competition, playing environment, and equipment [ 6 ]. Intrinsic factors can be further categorized as non-modifiable (e.g., genetics, anatomical characteristics, female gender) or modifiable (e.g., biomechanical factors like muscle strengthening, jumping, and landing techniques) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Various biomechanical risk factors have been identified, including increased knee and hip joint internal rotation, hip adduction, anterior tibial shear force, decreased knee flexion during landing, and increased knee valgus [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%